2015
DOI: 10.5116/ijme.5669.ea24
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ attitude towards bedside teaching in Tunisia

Abstract: ObjectivesTo assess patient' reaction towards bedside teaching at the University Hospital of Monastir (Tunisia) and to identify the factors that may influence it.MethodsA cross-sectional study was conducted during December 2012 at the University Hospital of Monastir. Each department, except the psychiatric department and the intensive care units, was visited in one day. All inpatients present on the day of the study were interviewed by four trained female nurses using a structured questionnaire.ResultsOf the 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 24 publications
4
27
2
Order By: Relevance
“…Although Vaughn et al argued about the lack of clear defined cut points between Education Research International 5 the positive and the negative perceptions, others like Simon et al found that patients' satisfaction did not increase or decrease when medical students were involved by using two controlled groups for assessment. This positive perception was consistent with previous studies that were done in Saudi Arabia and other Middle East countries [3,4,[12][13][14], keeping in consideration that those populations have to some extent similar cultural background and beliefs.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Although Vaughn et al argued about the lack of clear defined cut points between Education Research International 5 the positive and the negative perceptions, others like Simon et al found that patients' satisfaction did not increase or decrease when medical students were involved by using two controlled groups for assessment. This positive perception was consistent with previous studies that were done in Saudi Arabia and other Middle East countries [3,4,[12][13][14], keeping in consideration that those populations have to some extent similar cultural background and beliefs.…”
Section: Discussionsupporting
confidence: 92%
“…We found that 65.1% would allow medical students to present in the operation room. In comparison to Ben Salah et al they had a higher percentage (90.2%) regarding permitting the presence of medical students in the operation theatre [12] and the percentage was 57.7% in Marwan et al [14]. This perception led us to other essential queries about their perception about the medical students' role in the operating room.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…[ 6 ] Although patients feel compelled to let students observe them as they are being treated in a teaching hospital, they still have the right to decline the involvement of students whenever they feel uncomfortable. [ 7 ] Moreover, the participation of medical students in patient care may not be well received by the patients. [ 8 9 ] Literature suggests that the willingness of patients to discuss their personal information and to be examined by medical students is often affected by their sociocultural background and educational levels.…”
Section: Introductionmentioning
confidence: 99%